The Efficacy of Picture Series from Popular Indonesian Fairy Tales in Improving Year 11 Students' English-Speaking Skills - Nurjihan Nabilah Noor; Chairil Anwar Korompot; Sultan Baa (Journal of Excellence in English Language Education, 2023)
This study aimed to determine whether the picture series from popular Indonesian fairy tales improved Year 11 students' English-speaking proficiency. A pre-experimental study involving one group pre-test and post-test, this research was carried out at SMAN 1 Tinambung, a public senior high school in the Polewali Mandar Regency, West Sulawesi Province, Indonesia, in the 2021-2022 academic year. The sample of this research was Year 11 students who were recruited using a cluster random sampling technique. The respondents were chosen from a class consisting of 30 students. Employing quantitative methods, the researchers used a speaking test as a research instrument. The data collection technique was a speaking test administered to the students as a pre-test and a post-test. The students' speaking ability scores from the pre-test to the post-test showed a significant difference. It was found that (t = -9.635, p = 0.0005) was 0.000 < 0.05. The students' speaking improvement scores from the pre-test to the post-test showed a significant difference. The results showed that the mean value of the pre-test was 42.53 with a standard deviation of 13.14, while the average value of the post-test was 57.33 with a standard deviation of 8.55. The findings mean there is an increase in the English-speaking skills of SMAN 1 Tinambung students thanks to the use of picture series from popular Indonesian fairy tales. This finding shows that applying picture series from popular Indonesian fairy tales effectively improved the students' English speaking skills.